Rebundling higher educational research, teaching and service - Erik Blair (Linköping University Electronic Press, 2018)
Higher educational research has been bashed for its aloofness and isolation as individuals question its impact and its worth. This essay aims to highlight how the unbundling of academia, where research has become separate from teaching and service, has left a reduced conception of educational identity in the higher education sector. In becoming isolated, research has become an easier target. Instead, it is proposed that rebundling the three core aspects of higher education - research, teaching and service - would allow for a more holistic conception of academic identity where the various components work together to offer a more robust, and less 'bashable', academic identity.